Faunistic studies of the tribe Brachinini (Carabidae: Coleoptera) from northern Pakistan - Ullah, Mishkat; Naeem, Muhammad; Mahmood, Khalid; Rafi, Muhammad Ather (Zootaxa, 2017)
A faunistic study of the tribe Brachinini from northern Pakistan was carried out including extensive fieldwork collections and specimens housed in the Insect Repository, Pakistan Museum of Natural History, Islamabad and the National Insect Museum, National Agricultural Research Centre, Islamabad. Ten species belonging to three genera were identified from the study area, including four new records for Pakistan, Brachinus (Brachinus) ejaculans Fischer Von Waldheim, 1828, Brachinus (Neobrachinus) pallidipes Reitter, 1919, Pheropsophus (Stenaptinus) consularis (Schmidt-Goebel, 1846) and Pheropsophus (Stenaptinus) lineifrons Chaudoir, 1850. A key for these species is provided. A new combination is proposed for Brachinus (Brachynolomus) pallidipes Reitter, 1919, namely Brachinus (Neobrachinus) pallidipes Reitter, 1919, comb. nov.